2021
DOI: 10.1002/tsm2.226
|View full text |Cite
|
Sign up to set email alerts
|

In your shoes: A qualitative study on the perspectives of professional dancers and staff regarding dance injury and its prevention

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…It has been reported that athletes prefer that their healthcare providers understand and share their sport culture [ 46 ]. Athletes report that practitioners with experience in their sport, as a former athlete or as a practitioner, are considered to better relate and empathize with their situation [ 47 , 48 ]. It is possible that the appreciation for the athlete’s sport and their athletic culture may be a defining feature between sports chiropractors and general chiropractors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that athletes prefer that their healthcare providers understand and share their sport culture [ 46 ]. Athletes report that practitioners with experience in their sport, as a former athlete or as a practitioner, are considered to better relate and empathize with their situation [ 47 , 48 ]. It is possible that the appreciation for the athlete’s sport and their athletic culture may be a defining feature between sports chiropractors and general chiropractors.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence rates observed at the end of the season may be influenced by dancers who have been managing medical issues during the season. 15 However, it should be noted that mixed bill productions, which demonstrate an additional 2.3 medical attention injuries and 0.8 and time-loss injuries per 1000 hours compared to full-length stand-alone productions, are more common later in the season. While inter-season differences in medical attention injury incidence rates were seen, no clear pattern was observed across the five seasons, potentially due to inter-season variation in repertoire.…”
Section: Incidence Ratementioning
confidence: 99%
“…The severity of time-loss injuries within the present study is almost two-fold greater than the severity previously published in professional ballet, 1 similar to football, 33 and lower than rugby union, 28,30 and volleyball. 34 Professional ballet has previously been described as a culture that normalises pain, 15,35,36 which may result in dancers not reporting medical issues and dancing through discomfort. We observed that 56% of all days lost to time-loss injury were classified as 'restricted' as opposed to 'off', suggesting that dancers may still have been participating in some form of dance activity while injured.…”
Section: Severitymentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Findings from qualitative research indicate that coaches, health professionals and athletes acknowledge the importance of injury prevention as a means to achieve the best performance, taking into consideration their elite sport context. 19–21 However, the preventive measures described in such studies are related with open and effective communication, teamwork and empowering athletes rather than the exercise-based interventions widely documented in our literature. 22 23 Qualitative research methods 4 24 provide insight into the meaning and understanding of the contextual factors and can help us understand how and why injury prevention is adopted (or not) in the context of elite sports.…”
Section: Introductionmentioning
confidence: 99%